ANALYSIS OF THE IMPACT OF SIDE OBSTACLES ON ROAD PERFORMANCE: CASE STUDY OF THE KADIPATEN TRADITIONAL MARKET OF MAJALENGKA - Adhitya Akta Permana; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2024)
The discrepancy between the rise in automobile ownership and the suboptimal capacity of roads can be attributed to the escalating demands for transportation and the elevated purchasing power of individuals. This situation is particularly prevalent in high social and economic activity, such as the Kadipaten Traditional Market area, leading to frequent side obstacles. These obstacles, occurring in the market area, can be assessed based on various factors including pedestrian crossings, parked vehicles, vehicle flow in and out of the area, and slow-moving vehicles. This study aims to analyze the impact of side obstacles, traffic density, and road performance in the Kadipaten Traditional Market area. The research was conducted in three phases: the initial study, volume survey, and side obstacle assessment. This study utilizes primary and secondary data. The primary data encompasses the count of side obstacles and the traffic flow volume within the research area, which is subsequently computed and examined. The secondary data was sourced from the Central Statistics Agency for Majalengka city, encompassing population statistics, and then analyzed by the 2023 Indonesian Road Capacity Guidelines. Based on the findings, the saturation level was determined to be 0.615, indicating a moderate level of saturation as per the 2023 Indonesian Road Capacity Guidelines. This suggests that while traffic flow in the Kadipaten Traditional Market area is dense but relatively smooth, the presence of side obstacles significantly hampers road performance.